The importance of revenues from local fees in financing municipalities in Poland - Dziuba, Jarosław; Życzkowska, Elżbieta (Znaczenie dochodów z opłaty miejscowej w finansowaniu gmin w Polsce, 2022)
The article discusses the legal structure of the local fee and presents a multi-faceted statistical analysis, in terms of quantity and value, covering the application of this fee by the municipalities in Poland. The purpose was to present and assess the importance of this fee in financing municipalities. The study concerns revenues of all municipalities in Poland in the period 2014-2020. The conducted analysis shows that, generally, the local fee is not a common and significant source of financing the municipal sector. However, the examples of a few units indicate its high potential in generating revenues, thus after introducing the appropriate legal changes in the fee structure it should be used to a greater extent. This fee represents a desirable public levy which can fulfil important fiscal and non-fiscal functions resulting from its structure.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2022; vol. 66, nr 2, s. 29-46
Keywords: local self-government; local finance; public revenue; public levy; local fees; samorząd terytorialny; finanse lokalne; dochody publiczne; opłata publiczna; opłata miejscowa